The Effect of a Spaced Repetition System on EFL Students' Vocabulary Mastery: A One-Group Pretest-Posttest Study - Nurohmat Nurohmat; Dian Subagio (Wanastra: Jurnal Bahasa dan Sastra, 2026)
Mastering vocabulary is essential for successful English language learning, as it enables learners to understand and produce language effectively. Nevertheless, numerous English as a Foreign Language (EFL) students find it difficult to retain newly learned vocabulary due to limited exposure and infrequent review. This research aimed to examine how effective the Spaced Repetition System (SRS) is in enhancing students' vocabulary mastery. A pre-experimental design with a one-group pretest-posttest approach was employed. The participants were 50 Indonesian EFL students recruited from a senior high school located in West Jakarta. Data were gathered through vocabulary tests administered both before and after a six-week period during which SRS-based learning activities were implemented. The collected data were analyzed using descriptive statistics and a paired-samples t-test. The results showed a substantial improvement in students' vocabulary scores following the treatment (mean pretest = 62.48, mean posttest = 81.76, p < 0.001, t = -15.67, Cohen's d = 2.41). The average posttest score exceeded the average pretest score, suggesting that SRS usage was associated with vocabulary gains. These findings provide preliminary evidence that exposing students to vocabulary repeatedly at progressively longer intervals may help them remember words more effectively. However, due to the limitations of the pre-experimental design without a control group, these results should be interpreted cautiously and require confirmation through further research with more rigorous designs.